Analysis of physicochemical properties during the processing of Yiluxian, a traditional chinese low‐salt fish product. (14th July 2016) - Hao, Zina; Dong, Hao; Li, Zhenxing; Lin, Hong
Abstract: Yiluxian, a traditional Chinese low‐salt fish product, has been produced manually for decades. However, its quality depends on worker experience and varies owing to the lack of specific scientific guidelines for uniform production. This study investigated the changes in physicochemical properties under different salt concentrations and explored the principles underlying the low‐salt pickling process. The NaCl content of gutted fish increased to 3.82% in brining, and it decreased significantly to 1.15% after desalting. The colour of Yiluxian was not significantly different from that of raw fish ( P > 0.05). The hardness, springiness, resistance and chewiness decreased by 12%, 9%, 27% and 19%, respectively, while cohesiveness did not change significantly ( P > 0.05). Furthermore, Yiluxian is preferred over commonly salted fish for superior sensory profile. Our findings demonstrated the changes in various characteristics during pickling were expected to facilitate the stabilisation and uniformity of the quality and industrial production of this traditional food product. Abstract : Flesh without the skin of ice fresh Japanese seabasses were disposed during two stages: brining and desalting. Samples were picked out at 0, 24, and 48 h of brining and immersed in distilled water at a ratio 1:10 (fish:water, w/v) for desalting. This study investigated the changes in physicochemical properties under different salt concentrations and explored the principles underlying the low‐salt pickling process.